2017
DOI: 10.1177/1010428317740296
|View full text |Cite
|
Sign up to set email alerts
|

Association of mitochondrial copy number variation and T16189C polymorphism with colorectal cancer in North Indian population

Abstract: Globally, colorectal cancer is the third most common type of cancer. Genetic instability leading to cancer development is one of the major causes for development of cancer. Alterations in mitochondrial genome, that is, mutations, single-nucleotide polymorphisms, and copy number variations are known to contribute in cancer development. The aim of our study was to investigate association of mitochondrial T16189C polymorphism and copy number variation with colorectal cancer in North Indian population. DNA isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Mitochondria are responsible for ATP (energy) generation, reactive oxygen species generation and detoxification, and other essential functions in the cell 38 . Mitochondrial copy number alterations have been linked to autism 39,40 and multiple types of cancer including breast cancer 41,42 , bladder cancer 42 , kidney cancer 42 , and colon cancer 43,44 . Thus for example, our mitochondrial DNA quantification assays could be adapted to measure such mt copy number alterations in biofluids (e.g., urine, blood, cyst fluid, and cerebrospinal fluid) in cancer patients as a biomarker approach.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are responsible for ATP (energy) generation, reactive oxygen species generation and detoxification, and other essential functions in the cell 38 . Mitochondrial copy number alterations have been linked to autism 39,40 and multiple types of cancer including breast cancer 41,42 , bladder cancer 42 , kidney cancer 42 , and colon cancer 43,44 . Thus for example, our mitochondrial DNA quantification assays could be adapted to measure such mt copy number alterations in biofluids (e.g., urine, blood, cyst fluid, and cerebrospinal fluid) in cancer patients as a biomarker approach.…”
Section: Discussionmentioning
confidence: 99%
“…These regions are associated with mitochondrial genome instability [113,114]. Multiple other hotspots have been identified in the D-loop region including the T16189C polymorphism in endometrial cancer [115], rectal cancer [116], melanoma [94], and prostate cancer [117,118]. Interestingly, this SNP has been associated with metabolic disease and type II diabetes [119,120], further supporting a linkage between mitochondrial polymorphisms, metabolism and neoplastic development.…”
Section: Mitochondrial Haplogroups and Cancermentioning
confidence: 99%
“…Previous studies suggested that certain polymorphic mtDNA positions may be associated with increased risk of colorectal cancer in Iranian, Indian or European Americans [16][17][18][19][20]. In contrast, the studies performed on other ethnic groups (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…As mtDNA allele and haplogroup frequencies highly vary between different populations, it is important to evaluate the genetic risk of cancer in a specific ethnic context. To date, several studies have been carried out to investigate the associations of single mitochondrial DNA polymorphic sites (SNPs) with colorectal cancer in different ethnic groups [15][16][17][18][19][20]. The analysed SNPs were hotspots or positions diagnostic for major haplogroups.…”
Section: Introductionmentioning
confidence: 99%